Colombia : Selected Issues Paper. (IMF Staff Country Reports; Country Report ;, 2010)
This Selected Issues paper on Colombia shows that achieving investment grade status would help lower financing costs for the sovereign, and expand the pool of potential buyers of the Colombian economy. Colombia's debt levels as of end-2008 were broadly similar to the average for investment grade emerging markets, suggesting that other indicators are taken into account in rating agencies' assessments. A stronger process of fiscal consolidation that results in a significant decline in public sector debt could help compensate the structural weaknesses.